Persepsi Masyarakat Tentang Wakaf Uang Di Desa Lubuk Paku Kecamatan Batang Merangin Kabupaten Kerinci Provinsi Jambi - Kroillah Maysitah; Suhar Suhar; Sri Rahma (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study aims to determine the extent to which the perception of the people of Lubuk Paku village, Batang Merangin sub-district, about cash waqf, to find out what obstacles affect people's perceptions of cash waqf in Lubuk Paku village, Batang Merangin sub-district and to find out what problems are experienced by managers regarding the benefits of waqf money in lubuk kuku village. The benefits of this research are theoretically expected to add to the treasury of knowledge about waqf, especially cash waqf. Practically as input for waqf management institutions in socializing cash waqf to the public. This research is a field research using data collection techniques by interview, observation and documentation. Interviews and observations were conducted with the people of Lubuk Paku Village, Batang Merangin District. All the data generated then researchers analyzed with qualitative analysis techniques. From the research results it is known that some people regarding cash waqf from their own understanding or understanding and there are still many people who do not know cash waqf as a whole. Obstacles that affect people's understanding of cash waqf are internal constraints, namely experience and information. Then the second obstacle is external factors, namely education and the environment. People who have a higher level of education have a better understanding of cash waqf compared to people who have a low level of education and the management of implementing cash waqf in Lubuk Paku village, Batang Merangin sub-district, is not optimal, the reason is the lack of human resources in providing socialization and educate the public about the importance of cash waqf. cash waqf.